O problema do Paralelismo Psicofisiológico segundo a Epistemologia Genética - Pessoa, Kátia Batista Camelo [UNESP] (2014)
In this work we analyze how Piaget explains the nature of the relations between the structures of conscious actions and the physiological mechanisms that accompany them, for this is a problem common to many areas of knowledge, specially to Psychology and, more specifically, to Genetic Psychology and Genetic Epistemology. The solution of corresponding the structures of consciousness to the organic structures does not explain the nature of this link, because, with mere correspondence, if consciousness is only the subjective aspect of certain nervous activities, so does not comprehend which one is the function of consciousness. In the case of Parallelism, a psychophysiological correspondence is sought and a principle of psychophysiological isomorphism is invoked. It arises, therefore, a problem to Parallelism, that is show how two parallel structures act one on another. Our main goal with this research is to explain which is the problem put by Piaget and its solution: the hypothesis, proposed by him is that the parallelism between the states of consciousness and the concomitant physiological processes must be understood in terms of a partial isomorphism between the systems for implications in the broad sense and causalitydependent systems. It is necessary to explain how, clarifying the mode of such correspondence occurs, once there is no interaction exactly between the two heterogeneous structures, the of consciousness and the neurophysiological. After all, as Piaget says, consciousness is nothing or it depends on original and specific categories. We seek to show how Piaget comes to a third way of solution: the comprehension of the brain’s operation depends on the causal structures built by scientists, while knowledge-subjects, and represented in abstract models, including scientific theories. In this sense, implication is an original and specific category of conscious processes and the scientists judge the implications which arise...